124k views
3 votes
-2(x - 8) + 4x = -12

- 2x - 16+ 4x = -12
-2x - 16+ 4x = -12
- 2x - 16 = - 12
+16 +16
-2x
=
4
=2

User Hunter
by
6.0k points

2 Answers

3 votes

Answer:

x=14

Explanation:

User Vkstream
by
5.7k points
2 votes

Answer:

x = 14

Explanation:

Solve for x:

4 x - 2 (x - 8) = -12

-2 (x - 8) = 16 - 2 x:

4 x + 16 - 2 x = -12

4 x - 2 x = 2 x:

2 x + 16 = -12

Subtract 16 from both sides:

2 x + (16 - 16) = -16 - 12

16 - 16 = 0:

2 x = -16 - 12

-16 - 12 = -28:

2 x = -28

Divide both sides of 2 x = -28 by 2:

(2 x)/2 = (-28)/2

2/2 = 1:

x = (-28)/2

The gcd of -28 and 2 is 2, so (-28)/2 = (2 (-14))/(2×1) = 2/2×-14 = -14:

Answer: x = -14

User Asachet
by
5.4k points